Tractography-based navigated TMS language mapping protocol - Reisch, Klara; Böttcher, Franziska; Tuncer, Mehmet S.; Schneider, Heike; Vajkoczy, Peter; Picht, Thomas; Fekonja, Lucius S. (Frontiers in Oncology, 2022)
This study explores the feasibility of implementing a tractography-based navigated transcranial magnetic stimulation (nTMS) language mapping protocol targeting cortical terminations of the arcuate fasciculus (AF). We compared the results and distribution of errors from the new protocol to an established perisylvian nTMS protocol that stimulated without any specific targeting over the entire perisylvian cortex. Sixty right-handed patients with language-eloquent brain tumors were examined in this study with one half of the cohort receiving the tractography-based protocol and the other half receiving the perisylvian protocol. Probabilistic tractography using MRtrix3 was performed for patients in the tractography-based group to identify the AF’s cortical endpoints. nTMS mappings were performed and resulting language errors were classified into five psycholinguistic groups. Tractography and nTMS were successfully performed in all patients. The tractogram-based group showed a significantly higher median overall ER than the perisylvian group (3.8% vs. 2.9% p < .05). The median ER without hesitation errors in the tractogram-based group was also significantly higher than the perisylvian group (2.0% vs. 1.4%, p < .05). The ERs by error type showed no significant differences between protocols except in the no response ER, with a higher median ER in the tractogram-based group (0.4% vs. 0%, p < .05). Analysis of ERs based on the Corina cortical parcellation system showed especially high nTMS ERs over the posterior middle temporal gyrus (pMTG) in the perisylvian protocol and high ERs over the middle and ventral postcentral gyrus (vPoG), the opercular inferior frontal gyrus (opIFG) and the ventral precentral gyrus (vPrG) in the tractography-based protocol. By considering the white matter anatomy and performing nTMS on the cortical endpoints of the AF, the efficacy of nTMS in disrupting patients’ object naming abilities was increased. The newly introduced method showed proof of concept and resulted in AF-specific ERs and non-invasive cortical language maps, which could be applied to additional fiber bundles related to the language network in future nTMS studies.